Ancient Grains: New Evidence for Ancestral Puebloan Use of Domesticated Amaranth. Issue 4 (October 2021) - Turner, Michelle I.; Adams, Karen R.; Berkebile, Jean N.; Dockter, Abigail R.
Abstract : We report here the first domesticated amaranth ( Amaranthus spp.) seeds to be identified at a Chacoan great house, from the northern New Mexico site known as Aztec North, where they were found in a context that dates to the mid to late twelfth century AD. Amaranth has long been recognized as an important prehispanic resource in this region, evidenced by the archaeological record of both wild and domesticated forms and by the traditional knowledge and practices of Indigenous communities. Wild amaranth and similar-appearing chenopod/goosefoot ( Chenopodium spp.) seeds are routinely found in Ancestral Puebloan contexts. Recent archaeological testing at the Aztec North great house, a Chaco Canyon outlier associated with a post-Chacoan political center, has revealed the presence of uncharred domesticated amaranth seeds in a thin layer of ashy trash in a room at the rear of the great house. These seeds expand our understanding of domesticated amaranth in the American Southwest and suggest centuries of continuity of traditional amaranth cultivation within Puebloan communities.